Logistics Innovation in Developing Economies: Integrating Digital Solutions in E-Commerce Supply Chains - Setiadi; Muharam, Husni (Sinergi International Journal of Logistics, 2024)
The rapid expansion of e-commerce has created new challenges and opportunities for logistics systems in emerging markets. This study presents a narrative review exploring how logistics strategies have adapted to these shifts, with a focus on technological integration, collaboration models, financing mechanisms, and regulatory environments. Literature was gathered from Scopus and Google Scholar using targeted keywords related to e-commerce logistics and emerging markets. Inclusion criteria prioritized peer-reviewed articles from 2010 onward that addressed the intersection of logistics, digital technologies, and developing country contexts. Findings show that collaboration between e-commerce platforms and third-party logistics providers enhances operational efficiency, particularly through resource sharing and system integration. Technologies such as artificial intelligence, Internet of Things, and big data are instrumental in real-time route optimization and supply chain responsiveness. Financing models, particularly platform-based investments, have enabled digital upgrades and capacity expansion among logistics providers. Cross-border logistics adaptation and consumer-centric delivery services also emerged as key themes. However, systemic barriers including infrastructural deficits and regulatory fragmentation continue to hinder progress. The review underscores the importance of policy support and integrated technological adoption in enabling sustainable logistics transformation. It concludes by calling for future research on localized consumer dynamics, long-term impacts of digitalization, and inclusive financial frameworks to address existing gaps and strengthen the global competitiveness of e-commerce in emerging economi.